Strategic Trade Policy in General Oligopolistic Equilibrium - Rudy Colacicco (FIW - Research Centre International Economics, 2013)
In a two-country general oligopolistic equilibrium model, I study how cross-sector strategic trade policy affects wages, countrywide profits, and welfare. Firms face resource constraints and wages are simultaneously determined. Relative to free trade, cross-sector protectionism generates a reduction in the foreign wage without affecting the domestic wage. Domestic countrywide profits benefit from small import tariffs, whereas the foreign counterpart is hit, but when sectors share the same technology. Domestic welfare is unambiguously penalized. Hence, the general-equilibrium cross-sector perspective goes against the textbook version theory of the optimal tariff in partial equilibrium. Rationalization of these effects suggests a political-economy view on tariff formation in general equilibrium.
Keywords: D43; D51; F12; F13; L11; L13; 330; Cournot Competition; Home Market; Import Tariff; Income Distribution; Welfare